“To Separate Myself from Them, I Think I Will Feel Great Sadness”: Transnational Fatherhood and Border Regimes in Central Mexico - Alison Elizabeth Lee; Mario Alberto Macías-Ayala (Latin American Research Review)
Studies of fatherhood in Latin America demonstrate an uneven shift from traditional, patriarchal fatherhood to a more reflexive version that incorporates elements of active, relational fatherhood. This hybrid fatherhood emerged from the transition of Fordism to flexible accumulation, a transformation that coincided with massive migration from Central Mexico to the United States. Migration scholars have demonstrated the fluidity of masculine identities, men’s strategies to father across borders, and how US immigration enforcement shapes gendered subjectivities and power relations in transnational families. Building off these insights, we examine how return migrant men in rural central Mexico navigated changing meanings and practices of fatherhood. Their hybrid strategies reflect the inherent contradictions of a border regime that limited circular migration to the United States and their interest in maintaining close emotional attachments to children. Transnational fathers’ connections to reproduction reveal another way that affect articulates with capital accumulation and borders.